(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role and importance of foreign languages in the development of the vocational education system. In today's globalization environment, a qualified specialist must have not only professional knowledge and skills, but also the competence to communicate in foreign languages. Mastering foreign languages allows students to directly study modern technologies, international standards and best practices. Also, foreign languages increase the competitiveness of graduates of vocational education institutions in the labor market, create a basis for their participation in foreign companies and international projects. The article pays special attention to the issues of integrating vocational disciplines with foreign languages, the CLIL approach and the development of language competence in practical training. The results of the study substantiate the need to develop foreign languages as an important component of vocational education.